The Influence of Islamic Leadership Style and Knowledge Sharing on the Implementation of Learning Organizations in Improving Employee Performance - Nur Indah Sari; Yunus Amar; Mursalim Nohong (Magister Management, Hasanuddin University, 2021)
This study aims to determine the influence of Islamic leadership style and knowledge sharing on the implementation of learning organizations in improving employee performance. This research was conducted at PT. Bank Syariah Indonesia Kendari MT Haryono Branch Office. The study applied saturated samples of 35 employees. Data was collected using questionnaires with five Likert scales and analyzed with the use of path analysis after testing for validity and reliability. The results of this study indicate that Islamic leadership and knowledge sharing have a positive and significant effect on learning organizations. However, it was found that Islamic leadership has shown a positive and insignificant effect on employee performance. Knowledge sharing and learning organizations have a positive and significant effect on employee performance.